Wind Power for Irrigation Water Pump a Case study in Gedangan village - Benny Syahputra; Nafiah . (International Conference on Coastal and Delta Areas, 2015)
Water is a vital thing for the rice field. Field will never able to produce rice withoutsufficient water. Some methods are used to irrigate rice field, among others by using water pump, the method that also have been used in Gedangan village, Distric of Rembang, Nothern-East of Central Java Province. Based on data issued by Institute for Environment and Agricultural Research in 2010, the annual wind speed in the agricultural area of Gedangan village, minimum is 2.3 m/s and maximumis 9.2 m/s. This paper reported the study of using the prevailing wind speed to power the water pump for rice field irrigation purpose in Gedangan village. The combination between design and experimental were used in this study. In the experimental works were found that independent variable, such as wind speed and the revolution speed of the windmill, and dependent variable, such as amount of water flow out from the pump, have a relationship. The results show that wind power, with the above prevailing wind speed, only possible to power the water pump to irrigate the small-area of rice field.